The analysis of labor force participation in rubber smallholding sector in Banyuasin Regency, South Sumatera, Indonesia - M. Yusuf; Jamalludin Sulaiman (Journal of Economics, Business, and Accountancy Ventura, 2015)
The fact is that natural rubber has a strategic role as it is one of the commodities industry tropical crops. In addition, it also has important and strategic role in sup-porting the national economy, primarily as a source of livelihood of millions of rub-ber farmers in rural areas. This study analyzed the potential of using family labor in rubber smallholding sector in Banyuasin Regency, South Sumatra Province, Indo-nesia. The total sample used for the study was 280 respondents of households. Data was analyzed using multiple regression analyses. The multiple regression analysis used to identify the determinants of labor force participation decision regarding work in the rubber smallholding in the study area such as rubber production (kg per year per hectare), number of family workers, age of family head, location of dwelling, education of family head, and average years of schooling of family workers. Based on the analysis, only two factors affected significantly family labor force participation outside their smallholdings, namely number of family labor and education of family head.